Hukum Minimum Liebig - Sebuah Ulasan dan Aplikasi Dalam Biologi Kontemporer - Wendy Achmmad Mustaqim (Environmental Research Center (PPLH) of Udayana University, 2018)
Optimum plant growth depends on numerous ecological factors. In relation to this theme, there is an old law called Law of the Minimum Liebig. The postulate discussed the growth of the plant that is determined by the scarcest environmental factors. It is one of the oldest ecological postulate proposed more than one and a half-century ago. It has become one of the most important foundations for agriculture and biology, even the in contemporary biology. This short review will provide the history, principles, development and criticism, and applications in some recent biological sciences, including evolution, conservation, ecological indicator and even climate change.